Iron-Dependent Trafficking of 5-Lipoxygenase and Impact on Human Macrophage Activation - Dufrusine, Beatrice; Di Francesco, Andrea; Oddi, Sergio; Scipioni, Lucia; Angelucci, Clotilde Beatrice; D'Addario, Claudio; Serafini, Mauro; Häfner, Ann-Kathrin; Steinhilber, Dieter; Maccarrone, Mauro; Dainese, Enrico (Frontiers in Immunology, 2019)
5-lipoxygenase (5-LOX) is a non-heme iron-containing dioxygenase expressed in immune cells that catalyzes the two initial steps in the biosynthesis of leukotrienes. It is well known that 5-LOX activation in innate immunity cells is related to different iron-associated pro-inflammatory disorders, including cancer, neurodegenerative diseases and atherosclerosis. However, the molecular and cellular mechanism(s) underlying the interplay between iron and 5-LOX activation are largely unexplored. In this study, we investigated whether iron (in the form of Fe3+ and hemin) might modulate 5-LOX influencing its membrane binding, subcellular distribution and functional activity. We proved by fluorescence resonance energy transfer approach that metal removal from the recombinant human 5-LOX, not only altered the catalytic activity of the enzyme, but also impaired its membrane-binding. To ascertain whether iron can modulate the subcellular distribution of 5-LOX in immune cells, we exposed THP-1 macrophages and human primary macrophages to exogenous iron. Cells exposed to increasing amounts of Fe3+ showed a redistribution (ranging from ~45% to ~75%) of the cytosolic 5-LOX to the nuclear fraction. Accordingly, confocal microscopy revealed that acute exposure to extracellular Fe3+, as well as hemin, caused an overt increase in the nuclear fluorescence of 5-LOX, accompanied by a co-localization with the 5-LOX activating protein (FLAP) both in THP-1 macrophages and human macrophages. The functional relevance of iron overloading was demonstrated by a marked induction of the expression of interleukin-6 in iron-treated macrophages. Importantly, pre-treatment of cells with the iron-chelating agent deferoxamine completely abolished the hemin-dependent translocation of 5-LOX to the nuclear fraction, and significantly reverted its effect on interleukin-6 overexpression. These results suggest that exogenous iron modulates the biological activity of 5-LOX in macrophages by increasing its ability to bind to nuclear membranes, further supporting a role for iron in inflammation-based diseases where its homeostasis is altered and suggesting further evidence of risks related to iron overload.